Systems Readiness for Improved Monitoring and Evaluation with Specific Reference to the Micro Small and Medium Enterprises Sector in Nigeria - Ilori, Emmanuel Idemudia; Dassah, Maurice Oscar; Iwu, Chux Gervase (Journal of Reviews on Global Economics, 2019)
The Federal Ministry of Industry, Trade and Investment (FMITI) is mandated by law to provide support services and creating conducive business environment that supports the transformation of both small and large scale industries in Nigeria. The FMITI mandate and task is facilitated through its subsidiary, the Small Medium Enterprises Development Agency of Nigeria (SMEDAN). This is against the background that the parastatal will facilitate development (if well supported) by triggering production, employment opportunities and growth. Especially in Nigeria, where the informal sector employs more people than the formal sector, but with declining affluences of micro and small businesses, questions must be asked concerning the effectiveness of the institution's programmes and policies in revitalising, sustaining as well as growing the micro, small and medium enterprises (MSMEs) sector. In this paper, literature on monitoring and evaluation (M&E), legislative framework linked to the functioning of small and medium business sector is extensively reviewed. Furthermore, this paper will critically evaluate SMEDAN mandate to provide support services that will transform the informal sector of the Nigerian economy using existing monitoring and evaluation systems of selected programmes and policies put in place by the agency to indicate readiness (or lack thereof) of the current system to further develop the micro, small and medium enterprises (MSMEs) sector of the economy. This paper adopts qualitative and quantitative methodologies. It is anticipated that findings from this research-based paper will present lessons which can be harnessed to better reposition monitoring and evaluation systems hence, ensure effectiveness of future programmes and policies that will generate employment opportunities through SMEDAN.